Exploring the Link Between Reading Self-Efficacy and Comprehension: A Study on Chemical Engineering Students - Laili Inayatus Sholihah; Yudi Juniardi (AL-ISHLAH: Jurnal Pendidikan, 2025)
English proficiency is vital for chemical engineering students to access scientific literature and technical documentation. Among the critical skills, reading comprehension plays a central role. This study investigates the relationship between reading self-efficacy and reading comprehension in first-year chemical engineering students at Universitas Sultan Ageng Tirtayasa. A quantitative approach was employed, involving 66 participants. Data were gathered using a reading self-efficacy questionnaire and a standardized reading comprehension test. Pearson product-moment correlation analysis was conducted using Microsoft Excel to determine the relationship between the two variables. The analysis indicated a moderate positive correlation between reading self-efficacy and reading comprehension (r = 0.469). The p-value (7.04 × 10⁻⁵) was below the 0.05 threshold, confirming statistical significance. These findings suggest that students with higher confidence in their reading abilities tend to perform better in reading comprehension tasks. The results support the initial hypothesis that self-efficacy significantly influences reading comprehension. This underscores the need for instructional strategies that build students' confidence in reading. To enhance reading comprehension among chemical engineering students, educators should prioritize methods that foster reading self-efficacy. One effective approach is the use of top-down reading strategies, which encourage active engagement with texts and can improve both confidence and comprehension outcomes.